Fluorescence molecular tomography of DiR-labeled mesenchymal stem cell implants for osteochondral defect repair in rabbit knees - Berninger, Markus T.; Mohajerani, Pouyan; Kimm, Melanie; Masius, Stephan; Ma, Xiaopeng; Wildgruber, Moritz; Haller, Bernhard; Anton, Martina; Imhoff, Andreas B.; Ntziachristos, Vasilis; Henning, Tobias D.; Meier, Reinhard (European Radiology, 2017)
Objectives: To assess labelling efficiency of rabbit mesenchymal stem cells (MSCs) using the near-infrared dye 1,1’-dioctadecyl-3,3,3’,3’-tetramethylindotricarbocyanine iodide (DiR) and detection of labelled MSCs for osteochondral defect repair in a rabbit model using fluorescence molecular tomography–X-ray computed tomography (FMT-XCT). Methods: MSCs were isolated from New Zealand White rabbits and labelled with DiR (1.25-20 μg/mL). Viability and induction of apoptosis were assessed by XTT- and Caspase-3/-7-testing. Chondrogenic potential was evaluated by measurement of glycosaminoglycans. Labelled cells and unlabeled controls (n = 3) underwent FMT-XCT imaging before and after chondrogenic differentiation. Osteochondral defects were created surgically in rabbit knees (n = 6). Unlabeled and labelled MSCs were implanted in fibrin-clots and imaged by FMT-XCT. Statistical analyses were performed using multiple regression models. Results: DiR-labelling of MSCs resulted in a dose-dependent fluorescence signal on planar images in trans-illumination mode. No significant reduction in viability or induction of apoptosis was detected at concentrations below 10 μg DiR/mL (p >.05); the chondrogenic potential of MSCs was not affected (p >.05). FMT-XCT of labelled MSCs in osteochondral defects showed a significant signal of the transplant (p <.05) with additional high-resolution anatomical information about its osteochondral integration. Conclusions: FMT-XCT allows for detection of stem cell implantation within osteochondral regeneration processes. Key Points: • DiR-labelling of MSCs shows no toxic side effects or impairment of chondrogenesis. • Fluorescence molecular tomography allows for detection of MSCs for osteochondral defect repair. • FMT-XCT helps to improve evaluation of cell implantation and osteochondral regeneration processes.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cell labelling; Fluorescence molecular imaging; Mesenchymal stem cells; Osteochondral; Rabbit